SCIENTIFIC AND THEORETICAL BASIS OF STRENGTHENING THE REVENUE BASE OF LOCAL BUDGETS (World Economics and Finance Bulletin, 2024)
The scientific-theoretical basis of strengthening the revenue base of local budgets has been studied. The content and characteristics of local budgets are shown in detail. Also, the stages of formation of incomes of local budgets are mentioned.